Music for plants? an investigation into the impact of exposure to acoustic stimulus in Bok Choy (Brassica rapa) plants - Yeoh, Joanne Pei Sze; Zhang, Zixue; Koh, Khong Shien; Sinniah, Uma Rani; Spence, Charles; Beh, Wen Fen (Raiya Academic International LLC, 2024)
The study aimed to investigate the influence of different types of acoustic stimulus (classical vs. rock music) on the growth of bok choy (Brassica rapa) plants. Three separate groups of bok choy plants were exposed to classical music, rock music, or else no music, during growth and development and the influence on yield was observed. The results reveal that those plants exposed to classical music exhibited significant differences in shoot characteristics with the highest total fresh weight, shoot fresh weight, and mean leaf numbers. Meanwhile, those plants exposed to rock music demonstrated values that were the lowest across all plant parameters. Plants treated to classical music had the lowest root length but the highest root volume, indicating that the roots were significantly stouter and more compact as compared to those plants treated to rock music and no music. This study therefore serves as a future reference for the use of music in plant growth.